Development of a Computer-Based Format for the Alcohol, Smoking, and Substance Involvement Screening Test (ASSIST) With University Students. (28th July 2016) - Christoff, Adriana Oliveira; Barreto, Heloisa Gomm Arruda; Boerngen-Lacerda, Roseli
ABSTRACT: Background : The Alcohol, Smoking, and Substance Involvement Screening Test (ASSIST) is a reliable and valid tool for the early detection of harmful and hazardous drug use in primary care settings when administered by interview in the general population. In university students, substance use is high, so a reliable and feasible screening instrument is needed. Objectives : To compare the computer-based ASSIST (ASSISTc) with the interview format (ASSISTi). Methods : A convenience sample with counterbalanced design was used alternating between the ASSISTi and ASSISTc with 15-day interval. Although this is not a traditional test–retest reliability study, the same statistical analysis was used: intraclass correlations (ICC), kappa (κ), and Cronbach's alpha (α) to compare the two formats. A satisfaction questionnaire was applied immediately after the second session. Results : Both formats were completed by the students ( n = 809) over 15 days. The scores of involvement with all substances and with tobacco, alcohol, cannabis, and cocaine obtained with the two formats demonstrated excellent ICC (> .77). The level of agreement was considered substantial for tobacco (κ = .69) and cannabis (κ = .70) and moderate for alcohol (κ = .58). The consistency of the ASSISTc was considered satisfactory (α: .85 for tobacco, .73 for alcohol, and .87 for cannabis). The analysis of satisfaction and feasibility showed that the ASSISTi was easier to understand, but the two formats were considered similar when considering acceptability, ease of responding, and degree of intimidation. Conclusions/importance : The two formats are acceptable, the scores are comparable, and they can be used interchangeably.